2010
DOI: 10.1099/mic.0.037580-0
|View full text |Cite
|
Sign up to set email alerts
|

2,3-Dihydroxypropane-1-sulfonate degraded by Cupriavidus pinatubonensis JMP134: purification of dihydroxypropanesulfonate 3-dehydrogenase

Abstract: 2,3-Dihydroxypropane-1-sulfonate (DHPS) is a widespread intermediate in plant and algal transformations of sulfoquinovose (SQ) from the plant sulfolipid sulfoquinovosyl diacylglycerol. Further, DHPS is recovered quantitatively during bacterial degradation of SQ by Klebsiella sp. strain ABR11. DHPS is also a putative precursor of sulfolactate in e.g. Ruegeria pomeroyi DSS-3. A bioinformatic approach indicated that some 28 organisms with sequenced genomes might degrade DHPS inducibly via sulfolactate, with three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 30 publications
1
68
0
2
Order By: Relevance
“…In the case of catabolic genes, those encoding conserved central metabolic pathways are generally well characterized, but pathways for upstream reactions that ultimately feed into central metabolism, the linchpins of many essential biogeochemical transformations, are poorly known. When we are ultimately successful in identifying a new biogeochemically relevant gene, it is often the case that it was initially annotated with a misleading or uninformative function (89)(90)(91).…”
Section: How Many Metabolic Pathways Are Required For the Bacterial Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of catabolic genes, those encoding conserved central metabolic pathways are generally well characterized, but pathways for upstream reactions that ultimately feed into central metabolism, the linchpins of many essential biogeochemical transformations, are poorly known. When we are ultimately successful in identifying a new biogeochemically relevant gene, it is often the case that it was initially annotated with a misleading or uninformative function (89)(90)(91).…”
Section: How Many Metabolic Pathways Are Required For the Bacterial Tmentioning
confidence: 99%
“…A full suite of DMSP gene discoveries is now enabling studies of the dominant transformation pathways and their regulation in the ocean (94,95). Similarly, the genes mediating marine bacterial transport and metabolism of organic compounds such as sulfonates (90,96), ectoine and hydroxyectoine (97), and methylamines and choline (31,98,99) have been recently elucidated through model organism systems.…”
Section: How Many Metabolic Pathways Are Required For the Bacterial Tmentioning
confidence: 99%
“…Later work demonstrated that SQ can be degraded completely by two-member bacterial communities, that is, by a primary degrader with transient release of SL or DHPS and a secondary degrader with release of sulfate (11,12). Pathways for the degradation of DHPS and SL, including desulfonation, have been described (13,15,29) where, briefly, DHPS is oxidized to SL and the SL is mineralized via one of three known pathways and desulfonative enzymes [i.e., SL sulfolyase (SuyAB; EC 4.4.1.24), sulfoacetaldehyde acetyltransferase (Xsc; EC 2.3.3.15), cysteate sulfolyase (CuyA; EC 4.4.1.25)]. However, details on the pathways, enzymes, and genes for the conversion of SQ to DHPS and SL were missing.…”
Section: Matching Mass Of the [M-h]mentioning
confidence: 99%
“…The SLA is reduced to 2,3-dihydroxypropane sulfonate (DHPS) by the SLA reductase, and the DHPS is excreted (12). Hence, E. coli K-12 can use only half of the carbon in SQ and is not able to catalyze a desulfonation reaction, whereas other bacteria can degrade DHPS [or the 3-sulfolactate (SL) formed from SQ, as discussed below] completely, including desulfonation and release of sulfate, via defined pathways (MetaCyc pathway PWY-6616) (13)(14)(15). Thus, the sulfur cycle for SQ can be closed within bacterial communities (11, 12 and cf.…”
mentioning
confidence: 99%
“…S1). The enzymatic function of these bacterial genes was established previously (11,12), but their ecological role had remained unknown. Identification of both sulfonates as currencies in this model system suggests a diatom-derived oxidized organic sulfur pool that may be important in fueling the marine microbial food web.…”
Section: Significancementioning
confidence: 99%